A Catalogue of Orchids Recorded in Saranda Forest Division, West Singhbhum District, Jharkhand - Gupta, H. S.; Kumar, Ajay (Indian Forester, 2007)
Floristic bio-diversity is depleting alarmingly due to anthropogenic activities like encroachment and mining in Saranda. In recent years these activities have reached alarming levels such that many of the species of orchids are on the verge of extinction. An extensive survey and collection of specimens of 20 species of orchids was made in Saranda, West Singhbhum District, Jharkhand during the year 2003-2004. The results are reported in this paper.